Effect of short-term heat acclimation with permissive dehydration on thermoregulation and temperate exercise performance - Neal, R. A.; Corbett, J.; Massey, H. C.; Tipton, M. J. (Scandinavian Journal of Medicine & Science in Sports, 2016)
We examined the effect of short-term heat acclimation with permissive dehydration (STHADe) on heat acclimation (HA) and cycling performance in a temperate environment. Ten trained male cyclists [mean (SD) maximal oxygen uptake: 63.3(4.0) mL/kg/min; peak power output (PPO): 385(40) W; training: 10 (3) h/week] underwent a STHADe program consisting of 5 days of exercise (maximum 90?min/day) in a hot environment (40 °C, 50% RH) to elicit isothermic heat strain [rectal temperature 38.64(0.27) °C]. Participants abstained from fluids during, and 30 min after, HA sessions. Pre- and post-STHADe HA was evaluated during euhydrated fixed-intensity exercise (60 min) in hot conditions; the effect of STHADe on thermoregulation was also examined under temperate conditions (20 min fixed-intensity exercise; 22 °C, 60% RH). Temperate cycling performance was assessed by a graded exercise test (GXT) and 20-km time trial (TT). STHADe reduced thermal and cardiovascular strain in hot and temperate environments. Lactate threshold [ = 16 (17) W] and GXT PPO [ = 6 (7) W] were improved following STHADe (P < 0.05), but TT performance was not affected (P > 0.05), although there was a trend for a higher mean power (P = 0.06). In conclusion, STHADE can reduce thermal and cardiovascular strain under hot and temperate conditions and there is some evidence of ergogenic potential for temperate exercise, but longer HA regimens may be necessary for this to meaningfully influence performance.